The role of specialized media in developing the cognitive abilities of media students (National Geographic Channel Abu Dhabi as a model) (Journal of the College of Basic Education, 2023)
The media plays a pivotal role in the life of the individual, the family, the organization, society and the state, and in building states, civilizations and societies, and thus contributes to socialization and to the formation of public opinion and the collective memory of society. It also plays a strategic role in sustainable development in its various fields and sectors. Day after day, the important role played by the media in guiding, guiding and educating society becomes clear, in addition to the familiar role it plays in meeting the human need for communication, which is a human need that arose with the emergence of human societies, in order for the individual to communicate with other individuals and exchange information and ideas with them and express what he wants. In itself, humanity has known media since its inception and existence, and has practiced it in the methods that it has prepared for it and deemed suitable for it, then this process has evolved with the development of humanity and the discovery of different means and methods. Recently, the concept of media has expanded to include every method of collecting and transmitting information, experiences, opinions, ideas, and changing trends. As well as the transfer of customs and traditions.And after the fields of life multiplied and its fields diversified and its fields developed, specialization in life magazines, especially the media, became indispensable in pursuit of creativity in this field, familiarity with everything related to it, developing its horizons, and focusing on all its details and parts. Based on this, the field of mass media could not meet all the requirements of life, so the need arose for the presence of specialized media in different fields and areas of life, and it became vital for it, and necessary for understanding its components, sections, topics and events, a deep and comprehensive understanding, and from here this research came to shed light On the role of specialized media in developing the cognitive abilities of media students, specifically (National Geographic Abu Dhabi Channel films), which is considered a large part of specialized media.